BOOK REVIEW | Chemical Biomarkers in Aquatic Ecosystems - Christopher C. Parrish (Oceanography, 2012)
In order to measure inputs, cycling, and loss of material in aquatic ecosystems, a wide range of compounds and analytical tools is now available. Biological markers are compounds, or groups of compounds, that can be used as indicators or signatures of individual organisms or groups of organisms, or of certain environmental processes. Molecular biomarkers can be DNA fragments or smaller molecules that are easily determined using standard chromatographic techniques. Anthropogenic compounds can be used as wastewater markers to locate sources and pathways of transport as well as to determine pollutant loading.